Characterization of Tumor Responses in Patients With Unresectable Hepatocellular Carcinoma Treated With Lenvatinib in the Phase 3 Randomized Trial, REFLECT - Richard S. Finn; Shukui Qin; Fabio Piscaglia; Thomas R Jeffry Evans; Jennifer J. Knox; Carlos López López; Zahra Ramji; Min Ren; Kalgi Mody; Arndt Vogel; Masatoshi Kudo (Liver Cancer, 2024)
Introduction: In REFLECT, lenvatinib was noninferior to sorafenib in terms of overall survival (OS) in patients with unresectable hepatocellular carcinoma (uHCC; median 13.6 vs 12.3 months; HR 0.92, 95% CI 0.79-1.06). The objective response rate (ORR) with lenvatinib was 18.8% by blinded independent imaging review (IIR) per Response Evaluation Criteria in Solid tumors version 1.1 (RECIST v1.1); per modified RECIST (mRECIST), the ORR was 40.6%. We sought to further characterize these tumor responses and explore ORR’s importance among outcomes for patients with HCC.